Advancements and Challenges in Electric Vehicle Adoption in India - Pathak, Akanksha; Gangal, Vijay Kumar (Journal of Science & Technology, 2023)
The paper provides a comprehensive exploration of the factors influencing electric vehicle (EV) adoption in India, with a particular focus on barriers related to usability, infrastructure, safety, economics, and performance. The study employs various statistical methods to analyze and discuss the findings, offering valuable insights into the challenges and opportunities for EV adoption in Agra City. Agra city has a very low level of uptake of electric cars (ECs), despite significant efforts put in place by policy makers to stimulate their use. This paper investigates the barriers to wider EC adoption via a survey in May, 2023 to a representative sample (N = 165) of the population of Agra City. We discuss and rank the barriers, we discuss and rank the barriers on the basis of mean, tested H0: All types of barriers have an equal effect on buying decision, through Chi-Square test. Also we discuss and rank the barriers aggregate them via principal component analysis (PCA) on the basis of the Varimax Rotated factor analysis to study the socio-economic determinants of the respondents. The findings of this paper suggest a series of improvements that could be made by various key players. To overcome the Barriers related to usability (BU), Barrier of infrastructure (BI), Barriers related to safety and technology (BST), Barriers related to economic uncertainty (BEU) and Barriers related to performance (BRP), the policy makers should recommend car manufacturers to bring cars to the market with solutions to these factors for the wider adoption of electric cars.
Keywords: Electric cars; Barriers; Principal component analysis; Usability; Infrastructure; Economic uncertainty; Performance; Agra; Government policies